2021
DOI: 10.1177/1535370221995785
|View full text |Cite
|
Sign up to set email alerts
|

Going with the grain: Fiber, cognition, and the microbiota-gut-brain-axis

Abstract: Healthy dietary intake has been acknowledged for decades as one of the main contributors to health. More recently, the field of nutritional psychiatry has progressed our understanding regarding the importance of nutrition in supporting mental health and cognitive function. Thereby, individual nutrients, including omega-3 fatty acids and polyphenols, have been recognized to be key drivers in this relationship. With the progress in appreciating the influence of dietary fiber on health, increasingly research is f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 163 publications
(204 reference statements)
0
41
0
Order By: Relevance
“…The Mediterranean, vegetarian and vegan diets include a high amount of these foods [ 378 , 379 ]. High-fibre intake has been associated with intestinal health, improved bowel motility, low risk of intestinal inflammation and colorectal cancer, low cholesterol absorption and improvement in cognitive functions [ [379] , [380] , [381] ].…”
Section: Dietary Interventions That Act On Body Weight and That Shape...mentioning
confidence: 99%
“…The Mediterranean, vegetarian and vegan diets include a high amount of these foods [ 378 , 379 ]. High-fibre intake has been associated with intestinal health, improved bowel motility, low risk of intestinal inflammation and colorectal cancer, low cholesterol absorption and improvement in cognitive functions [ [379] , [380] , [381] ].…”
Section: Dietary Interventions That Act On Body Weight and That Shape...mentioning
confidence: 99%
“…This is predominately due to the action of specific bacteria in the gut on the production of several metabolites, such as short-chain fatty acids [112], that may influence the beneficial health patterns observed in the microbiotagut-brain axis. Although there is an increased connection between dietary fiber on overall mental health, only relatively few studies have explored the connection between dietary fiber and cognition, with mixed results [113].…”
Section: Grainsmentioning
confidence: 99%
“…According to the available data, increasing daily dietary fibre intake reduces the risk of cardiovascular-related issues, diabetes, and cancer. In addition to this, emerging evidence has shown that dietary fibre consumption patterns are linked to improved mental health [ 94 , 95 ] and other cognitive functions [ 96 ]. Because of this, it is vital that a better understanding of the mechanism behind fibre’s specific health benefits is established.…”
Section: Health Benefitsmentioning
confidence: 99%